Comparative Corrosion Inhibition Test Study in Phosphate Buffer Saline for 316L Stainless Steel with Electrospun PCL Coating with Different Additives - Ersin, Kamberli; Mothana Ghazi, Kadhim AlFalah; Fatma, Kandemirli (Everant Journals, 2024)
In this study, ten different contents of PCL-based nanofibers containing ZnO, CuO, NiO, 2F TSC, 4F TSC and graphite additives (PCL+Graphite+CuO+NiO+ZnO, PCL+ZnO+Graphite, PCL+ZnO+NiO+CuO, PCL+ZnO, PCL+Graphite, PCL+ZnO+2F TSC, PCL+ZnO+NiO+CuO+4F TSC, PCL+ZnO+NiO+CuO+2F TSC, bare PCL, PCL+ZnO+4F TSC) 316L stainless steel (SS) surface was coated. After coating with these different types of nanofibers, measurements were taken with electrochemical techniques such as potentiodynamic polarization (PDP) and electrochemical impedance spectroscopy (EIS) in phosphate buffer solution (PBS) for 1 hour to investigate the corrosion inhibition properties. According to the results, the PCL+Graphite+CuO+NiO+ZnO coating provided the highest corrosion inhibition with a protection efficiency value of 98.83%. The PCL+4F+ZnO coating had the lowest inhibition property with a protection efficiency value of 40.72%. At the end of the tests, Nyquist, Bode, Tafel, OCP diagrams of the coatings were obtained and equivalent circuit models were presented.
Keywords: EIS, corrosion inhibition, polymer coating